Tahap kemahiran employability pelajar Kejuruteraan dari perspektif majikan - Husain Mohd Yusof, Rasul Mohamad Sattar, Mustapha Ramlee, Malik Syed A., Abd Rauf Rose Amnah, (N/A, 2013)
Tahap kemahiran employability pelajar Kejuruteraan dari perspektif majikan by Husain Mohd Yusof, Rasul Mohamad Sattar, Mustapha Ramlee, Malik Syed A., Abd Rauf Rose Amnah,